(untitled) (The International Journal for Scientific Research, 2024)
Designers seek to create a design product that is dialogic and communicative with the largest number of segments of society, with visual formations that prepare for a spatial environment that is distinguished by intellectual richness and seeks to communicate with minds. Then, the design represents a visual discourse that influences the recipient, as an intentional message that reaches his imagination with its idea, including the aesthetic meanings inherent in it, and what its intellectual and semantic content carries, the aim of which is to reach a common meaning between the designer and the recipient so that the designer can lead the recipient’s behavior according to the ideas presented by the design. Therefore, the research problem was formulated with the following question: "Is interior design concerned with visual formations to highlight formal values ​​that aim to improve the aesthetic taste through the visual reception system of the recipient only, or is it an ideology that indicates that these formations are more than just what the eye sees because of their connection to the shared latent meaning between the designer and the recipient, which is reflected in the nature of collective behavior?" The research aimed to "reveal the data of the aesthetic image of the formal discourse by translating the latter into an internal space that gives the recipient interpretations that are in harmony with what the designer is going for as a directed message with intent and meaning." The research came out with a set of conclusions, the most important of which are: The design product constitutes a message with a clear meaning when it is a reflection of the social, cultural, material and geographical environment of the design context through the aesthetic formations of the design discourse, and that the reception mechanism is not destined to succeed unless the designer has a specific idea that reflects the privacy of society and the identity of the place through what the design broadcasts in order to obtain a clear and easy response from the recipient and decipher the symbols of the discourse and enjoy its connotations and goals.